2012
DOI: 10.1088/0953-8984/24/44/445001
|View full text |Cite
|
Sign up to set email alerts
|

The electronic and chemical structure of the a-B3CO0.5:Hy-to-metal interface from photoemission spectroscopy: implications for Schottky barrier heights

Abstract: The electronic and chemical structure of the metal-to-semiconductor interface was studied by photoemission spectroscopy for evaporated Cr, Ti, Al and Cu overlayers on sputter-cleaned as-deposited and thermally treated thin films of amorphous hydrogenated boron carbide (a-B(x)C:H(y)) grown by plasma-enhanced chemical vapor deposition. The films were found to contain ~10% oxygen in the bulk and to have approximate bulk stoichiometries of a-B(3)CO(0.5):H(y). Measured work functions of 4.7/4.5 eV and valence band … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 107 publications
(175 reference statements)
6
12
3
Order By: Relevance
“…Hydrogen is known to exhibit rare bridging B-H-B bonding in amorphous boron-based solids (Anan'ev et al, 2002), but since this is not observed spectroscopically, we assume its contribution is absent or negligible. Finally, we would be remiss to not mention oxygen, which is inevitably present in these a-BC:H films in concentrations ranging from ∼1-10% (Driver et al, 2012;Nordell et al, 2015). This element is found to exist in the form of OH groups, CO groups, and/or boron-oxide-based species, and is generally considered 2-fold coordinate.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen is known to exhibit rare bridging B-H-B bonding in amorphous boron-based solids (Anan'ev et al, 2002), but since this is not observed spectroscopically, we assume its contribution is absent or negligible. Finally, we would be remiss to not mention oxygen, which is inevitably present in these a-BC:H films in concentrations ranging from ∼1-10% (Driver et al, 2012;Nordell et al, 2015). This element is found to exist in the form of OH groups, CO groups, and/or boron-oxide-based species, and is generally considered 2-fold coordinate.…”
Section: Resultsmentioning
confidence: 99%
“…synthesized by CVD and PECVD are wide ranging [8,44,45]. This is represented by a-B 10 C 2+x :H y with 0 < x < 3 and 0 < y <12.…”
Section: Reported Stoichiometric Compositions Of Amorphous Hydrogenatmentioning
confidence: 99%
“…Semiconductor boron carbides have been shown to be suitable for semiconducting devices and solid state neutron detection [11][12][13][14][15][16][17][18][19][20][21][22][23]. Essential to any semiconductor device is the metal contact and the chemical interactions or band bending that may occur at the metal/semiconductor interface, so increasingly there has been investigation of the interface of various boron carbides to various metals [24][25][26][27]. Understanding the metal contacts on the surface of these semiconductors presents a number of important challenges.…”
Section: Introductionmentioning
confidence: 99%
“…As such, a fairly unreactive large work function metal contact, such as Au (with a work function in the range of 5.3 to 5.5 eV [31][32][33]) or Pt (with a work function in the range of 5.6 to 5.9 eV [33,34]), would be expected to form a Schottky barrier contact. Low work function metals have attracted much attention, but are often seen to be quite reactive at the interface with boron carbide [24]. A less reactive metal, with high work function, is an important juxtaposition, and may afford insight as to whether the formation of Schottky barrier contacts with PECVD hydrogenated semiconducting boron carbide is facile.…”
Section: Introductionmentioning
confidence: 99%